2019
DOI: 10.1055/s-0039-1683953
|View full text |Cite
|
Sign up to set email alerts
|

Knee Ultrasonography to Determine Risk for Noncontact Injuries in Collegiate American Football Players

Abstract: Knee ultrasonography has been used effectively as a screening tool for determining risk for knee injuries in athletes. Ultrasonography may be a valuable screening tool for relative risk of noncontact knee injuries that occur over a typical playing career in collegiate American football players. In this prospective longitudinal study, we evaluated American football players (n = 48) in an academic institution affiliated with the National Collegiate Athletic Association Division I athletic program. Players underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Additional analysis of our data was done among player groups, which showed no difference of IKDC-SKF score between ultrasonographic effusion positive and negative knees of players (77.82 vs 76.56, P=0.77, unpaired t-test). Also, in a longitudinal follow-up study of collegiate American football players by Lewis et al, there was no higher likelihood for developing knee injury in a 5-year career duration with effusion noted on pre-career ultrasonography screening [19].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Additional analysis of our data was done among player groups, which showed no difference of IKDC-SKF score between ultrasonographic effusion positive and negative knees of players (77.82 vs 76.56, P=0.77, unpaired t-test). Also, in a longitudinal follow-up study of collegiate American football players by Lewis et al, there was no higher likelihood for developing knee injury in a 5-year career duration with effusion noted on pre-career ultrasonography screening [19].…”
Section: Discussionmentioning
confidence: 90%
“…Our investigation also showed similar result. In previous study of Cook et al, in teenager basketball player aged 14-18 years, if asymptomatic patellar tendinosis is noticed in ultrasonography, there is 30% chance that symptoms will develop in the future, which is significantly higher compared with those who have normal ultrasonographic appearance (9%) [27] and Lewis et al also revealed that there was a significantly higher likelihood of patellar tendon injury based on the presence of patellar tendon ultrasonographic pathology and the odds ratio was 11 [19]. These findings made screening of asymptomatic patellar tendinopathy clinically relevant due to the impact on basketball player when it becomes symptomatic.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Anterior cruciate ligament (ACL) injuries are one of the most common and debilitating injuries of the knee (Montalvo et al, 2019). It accounts for one‐third of all knee injuries, requiring extensive rehabilitation, whether managed conservatively or following reconstructive surgery (Lewis et al, 2019). Not only are ACL injuries clearly associated with the young and active population, injury rates are gaining momentum within the adolescence group (Cruz, Pandya, Ganley, & Kocher, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 Similarly, numerous studies regarding the prevention and rehabilitation of musculoskeletal injuries in football have also been undertaken. 8 , 9 , 10 Interest in injuries sustained during the play of football is not concerning only to the academic community; indeed, football and the dangers that the game presents have become a prevalent concern among players, parents, and spectators alike.…”
mentioning
confidence: 99%